WebOPAC self-guided training tool with guided exploration manual for information literacy skills development - Ismail, Mohd Nasir; Mamat, Nurfaezah; Jamaludin, Adnan (Universiti Teknologi MARA, Kedah, 2017)
WebOPAC Self-Guided Training Tool with Guided Exploration Manual (WSGTTG) is a unique and novel interactive web-based tutorial application with guided exploration manual that helps individuals to be cognitively prepared to solve their problem in searching the information using the WebOPAC system. This WSTTG is also an instructional strategy which enables individuals to recognize information need and develop their ability to locate, evaluate, and use effectively the information needed. In addition, this tool has the capability to develop and access information literacy skill among library users in using WebOPAC system. Furthermore, this effective strategy has been developed according to the instructional design theories which comply with the ACRL Information Literacy Competency Standards for Higher Education and Bloom Taxonomy standard. This WSTTG can be commercialized as an instructional strategy for library orientation program and to be used by both the librarians and library users for WebOPAC teaching and learning purposes. The use of the WebOPAC Self-Guided Training Tool with Guided Exploration Manual as an instructional strategy will enable individuals to recognize information need and have ability to locate, evaluate, and use effectively the information needed is a novelty.